Optical stimulation systems for studying human vision - Barrionuevo, Pablo A.; Preciado, Oscar U.; Sandoval Salinas, María L.; Issolio, Luis A. (Circadian and Visual Neuroscience, 2022)
This chapter describes the most common setups that scientists use for generating light stimulation, from lab-made approaches to commercially available technologies. The studied optical stimulation systems are divided into nonimage-forming and image-forming arrangements. Two classical systems widely used are among the first: the Maxwellian view system and the Ganzfeld stimulator. Between the image-forming arrangements, the focus is on approaches that consider off-the-shelf devices and the recent appearance of multi-primary displays, which allow the inclusion of more primaries and the generation of stimulation for independent and combined photoreceptor and postreceptoral excitations. Some of the several limitations that can have important implications in research practice are also examined, such as those related to color gamut, sampling frequency, light range, and spatial resolution. Since experimentation on how optical radiation is processed by the human neural system requires the reliability of the parameters and variables under study to be assured, the characterization and consequent calibration of experimental devices are essential. Therefore the chapter discusses a set of characterization and calibration principles that researchers should consider when carrying out experiments with the described optical stimulators. Outstanding characteristics are stimulator response curve, primaries' spectral power distribution, additivity, modulation transfer function, and temporal stability. Finally, some possible sources of artifacts that researchers should consider when these stimulators are used are presented. Throughout this last section, data based on different optical stimulator measurements is provided.